Habits of Mind: Student Achievement in Mathematical Physics Courses - Pujayanto, Pujayanto; Adi, Delisma Wisnu; Hudha, Muhammad Nur (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Developing Habits of Mind (HOMs) is essential in higher education as it nurtures critical thinking and problem-solving skills. This study explores the correlation between HOMs and student achievement in the Mathematical Physics course. The research involved 78 undergraduate students from the Physics Education program at the Faculty of Teacher Training and Education, Universitas Sebelas Maret. The study utilised a student achievement test, designed and validated by experts based on learning outcomes, and a HOMs questionnaire covering self-regulation, critical thinking, and creative thinking dimensions. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0 to test the hypothesis that HOMs influence academic performance in Mathematical Physics. The model's validity was confirmed through Convergent Validity and Discriminant Validity assessments. Significance was assessed using the t-statistic and p-value to determine the statistical significance of the relationships between constructs. Results indicated that the measurement model met the validity criteria, with a T-Value of 15.927 (T-Value > 1.96), confirming a statistically significant relationship between HOMs and learning achievement at a 95% confidence level (alpha = 0.05). These findings underscore the significant impact of HOMs on student performance in Mathematical Physics. Integrating HOMs into the curriculum is recommended to improve learning effectiveness and student achievement in Physics. Furthermore, these results provide educators with a basis for developing more interactive teaching strategies that promote HOMs in students.